Natural photonics and bioinspiration - Mouchet, Sébastien R.; Deparis, Olivier (Norwood : Artech House, 2021)
Photonic structures occurring in biological tissues such as butterfly wings, beetle elytra or fish scales are responsible for a broad range of optical effects including iridescence, narrow-band reflection, large solid-angle scattering, polarization effects, additive color mixing, fluid-induced color changes, controlled fluorescence. Studies have provided understanding of the underlying optical mechanisms and the biological functions as well as inspiration for the design and development of novel photonic devices, also called bioinspiration. In this forward-thinking book, the research related to photonic structures in natural organisms is reviewed with a main foPhotonic structures occurring in biological tissues such as butterfly wings, beetle elytra, or fish scales are responsible for a broad range of optical effects including iridescence, narrow band reflection, large solid-angle scattering, polarization, additive color mixing, fluid induced color changes, and controlled fluorescence. This book reviews research of biological photonic devices in accordance with the fundamental aspects of physical optics and environmental biology. It provides readers with an understanding of numerical modelling based on morphological and optical characterizations as well as the quantitative treatment of color vision. This forward-thinking book ties these concepts to the design and synthesis of bioinspired photonic devices and opens the door to the applications of nature & rsquo;s lessons in the technical world. & nbsp; This resource introduces a methodology for working with and utilizing bioinspiration. It includes the experimental and numerical tools necessary for the characterization and simulation of photonic structures and uses original concepts as examples, with a focus on bioinspired hygrochromatic materials. Professionals are brought up to speed on a variety of fabrication techniques and methods of synthesis all following a straightforward bottom-up or top-down approach. The reader will gain an understanding of the capability of bioinspiration to meet human needs. This book & rsquo;s explanation of how natural photonics structures behave as efficient solar absorbers or thermal management devices makes it a useful resource for technical professionals in the field of energy and environment, and the concepts presented in this book also have applications in the designs of optical coatings, sensors, and light sources.
10.3 Sol-Gel Methods -- 10.4 Silicon Processing Technologies -- 10.5 Atomic Layer Deposition -- 10.6 Magnetron Sputtering -- 10.7 Processes Involving Cellulose Nanocrystals -- References -- CHAPTER 11 Ideas at Work: Bioinspired Hygrochromic Devices -- References -- CHAPTER 12 Bioinspired Applications in Photonics -- 12.1 Antireflective Coatings -- 12.1.1 Self-Assembled Coatings Inspired by Moth Eyes -- 12.1.2 Nanoimprinted Coatings from Cicada Wing Templates -- 12.2 Sensing -- 12.2.1 Gas and Vapor Sensing -- 12.2.2 Butterfly Wings as SERS Substrates -- 12.3 Light Harvesting -- 12.3.1 Solar Concentrators -- 12.3.2 Solar Light-Harvesting Structures -- 12.4 Light Extraction -- 12.5 Anticounterfeiting Patterns Inspired by Butterfly Scales -- 12.6 Conclusion -- References -- About the Authors -- Index.
Print version record.
eBooks on EBSCOhost
Keywords: Photonics; Photobiology; Photobiology; Photonique; Photobiologie; Photobiology; Photonics; Electronic book